Paralysed Patient Monitoring Kit (Parakit) - Ahmad Syahmi Adli, Shamsuddin (2023)
This report presents the results of a final year project aimed at helping paralyzed patients who live at home to monitor their health easily and accurately. The kit is known as the "Paralyzed Patient Monitoring Kit (PARAKIT)" and uses three sensors, namely the Pulse Rate Sensor, the Non-Contact Infrared Sensor, and the MQ135 Air Quality Sensor. Fuzzy Logic method is used to process data from the three sensors and determine the patient's current condition. The results show that PARAKIT is capable of processing data accurately and providing a precise analysis of the patient's health status. The kit is easy and practical to use because trained doctors or nurses only need to bring it to the patient's home and does not require complicated installations. This makes the kit very suitable for paralyzed patients who live at home and are unable to come to hospitals and health clinics for routine health checks. Overall, PARAKIT opens up opportunities for the development of more advanced and effective patient monitoring systems to monitor the health of paralyzed patients. This project is a crucial step in ensuring that paralyzed patients receive quality care and helping them to make useful preventive actions for their health.